Improving the Thermal Properties of Polycarbonate via the Copolymerization of a Small Amount of Bisphenol Fluorene with Bisphenol A - Xiaozhou Zhang; Yang Liu; Xin Li; Xin Liu; Xigao Jian; Jinyan Wang (International Journal of Polymer Science)
Polycarbonate is an attractive transparent plastic with high mechanical/thermal properties. A family of copolycarbonates of bisphenol-A (BPA), 9, 9-bis (4-hydroxyphenyl) fluorene (BHPF), and diphenyl carbonate (DPC) were prepared by a transesterification polymerization. The weight-average molecular weight of the polycarbonates ranges from 65,000 to 107,000 g/mol; the copolycarbonates showed Tg and Td−5% from 63-70°C and 100-105°C higher than the control, respectively. Meanwhile, the processing properties of polycarbonate remain unchanged. These properties endow the polymers with potential for use as high-temperature resistance materials.